Effect of Intracellular pH on Rotational Speed of Bacterial Flagellar Motors - Minamino, Tohru (American Society for Microbiology, 2003)
Weak acids such as acetate and benzoate, which partially collapse the transmembrane proton gradient, not only mediate pH taxis but also impair the motility of Escherichia coli and Salmonella at an external pH of 5.5. In this study, we examined in more detail the effect of weak acids on motility at various external pH values. A change of external pH over the range 5.0 to 7.8 hardly affected the swimming speed of E. coli cells in the absence of 34 mM potassium acetate. In contrast, the cells decreased their swimming speed significantly as external pH was shifted from pH 7.0 to 5.0 in the presence of 34 mM acetate. The total proton motive force of E. coli cells was not changed greatly by the presence of acetate. We measured the rotational rate of tethered E. coli cells as a function of external pH. Rotational speed decreased rapidly as the external pH was decreased, and at pH 5.0, the motor stopped completely. When the external pH was returned to 7.0, the motor restarted rotating at almost its original level, indicating that high intracellular proton (H(+)) concentration does not irreversibly abolish flagellar motor function. Both the swimming speeds and rotation rates of tethered cells of Salmonella also decreased considerably when the external pH was shifted from pH 7.0 to 5.5 in the presence of 20 mM benzoate. We propose that the increase in the intracellular proton concentration interferes with the release of protons from the torque-generating units, resulting in slowing or stopping of the motors.